P-block element catecholates: Lewis superacidic, constitutionally dynamic, and redox active - Greb, Lutz (Synlett, 2023)
Numerous strategies for enhancing the reactivity and properties of p-block elements have been devised in the past decades. This Account discusses our approaches by distinct ligand control on p-block elements in their normal (group) oxidation states. Catecholato ligands on silicon, germanium, or phosphorus produce a range of rewarding properties. Substantial electron withdrawal paired with structural constraint effects (influence of deformation energy) impart Lewis superacidity to these abundant elements. The ease of synthesis of such species facilitates screening in catalysis, promising a range of applications by powerful bond activation. Low-barrier Si-O/Si-O bond metathesis provides the most abundant bond in our Earth’s crust, with adaptive features under mild conditions, and establishes a new branch of constitutional dynamic chemistry. The redox-active character of catecholates grants access to novel compounds with tunable open-shell features. Overall, p-block catecholates offer unique opportunities due to their versatile features that will enrich the chemistry of the main-group elements.
Artikel online veröffentlicht: 29. August 2023
Gesehen am 16.10.2023